2017
DOI: 10.5041/rmmj.10296
|View full text |Cite
|
Sign up to set email alerts
|

Review of Robotic Surgery in Gynecology—The Future Is Here

Abstract: The authors present a systematic review of randomized and observational, retrospective and prospective studies to compare between robotic surgery as opposed to laparoscopic, abdominal, and vaginal surgery for the treatment of both benign and malignant gynecologic indications. The comparison focuses on operative times, surgical outcomes, and surgical complications associated with the various surgical techniques. PubMed was the main search engine utilized in search of study data. The review included studies of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 62 publications
(101 reference statements)
0
25
0
1
Order By: Relevance
“…23,2938 The incidence of overall complications in our cohort was much lower (8.2%)—similar to that reported for the general population (approximately 9%) in a recent review and meta-analysis of the literature. 39 , 40 This indicates that robotic surgery in the elderly appears to be feasible, with acceptable morbidity. In our study, we found no increased risk of overall complications within the three age groups examined.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…23,2938 The incidence of overall complications in our cohort was much lower (8.2%)—similar to that reported for the general population (approximately 9%) in a recent review and meta-analysis of the literature. 39 , 40 This indicates that robotic surgery in the elderly appears to be feasible, with acceptable morbidity. In our study, we found no increased risk of overall complications within the three age groups examined.…”
Section: Discussionmentioning
confidence: 98%
“…However, although we observed an unfavorable trend related to age, it is important to emphasize that the overall incidence of adverse events was comparable to that reported in the literature for similar age groups, as well as for the general population. 23 , 2940…”
Section: Discussionmentioning
confidence: 99%
“…Robotic myomectomy is more expensive compared to other surgical approaches, a fact restraining its access. Ultimately, randomised clinical trials (RCTs) are urgently needed to support the influx of data regarding the advantages of robotic surgery …”
Section: Evidence In Benign Gynaecological Surgerymentioning
confidence: 99%
“…Over the past 12 years, the da Vinci assisted approach to laparoscopic hysterectomy has taken a more prominent role in the surgical management of a multitude of benign and oncologic gynecologic conditions. Multiple meta-analyses and literature reviews have shown that the use of robotic surgery offers the advantage of decreased blood loss and length of stay when compared to open surgical techniques [5]. When compared to traditional laparoscopic methods outcomes appear to be equivocal, but a case can be made for the advantages of robotic surgery to treat obese patients [6].…”
Section: Introductionmentioning
confidence: 99%